2019
DOI: 10.1037/men0000182
|View full text |Cite
|
Sign up to set email alerts
|

Mental health promotion in male-dominated workplaces: Perspectives of male employees and workplace representatives.

Abstract: The workplace provides an important setting to promote men's mental health, yet few studies have explored the gendered views of men and workplace representatives in male-dominated industries about workplace mental health promotion. Consultations with working men (N ϭ 23) and interviews with seven representatives from male-dominated industries in northern British Columbia, Canada were conducted. Findings highlight the impact of masculine workplace cultures on men's mental health and practices that limit men's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 48 publications
(55 reference statements)
0
33
0
1
Order By: Relevance
“…In the present study, men who perceived their general health to be poorer as well as men who had higher levels of negative affect were more interested in activities related to managing stress. Here, it may be notable that we did not ask about "reducing" but about "managing" stress; recent qualitative research suggested the possibility that men may only talk openly about stress at work if they are perceived to be controlling it (Seaton, Bottorff, Oliffe, Medhurst, & DeLeenheer, 2018). The present results suggest that men who are likely feeling more stress are most interested in workplace activities related to managing stress.…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, men who perceived their general health to be poorer as well as men who had higher levels of negative affect were more interested in activities related to managing stress. Here, it may be notable that we did not ask about "reducing" but about "managing" stress; recent qualitative research suggested the possibility that men may only talk openly about stress at work if they are perceived to be controlling it (Seaton, Bottorff, Oliffe, Medhurst, & DeLeenheer, 2018). The present results suggest that men who are likely feeling more stress are most interested in workplace activities related to managing stress.…”
Section: Discussionmentioning
confidence: 61%
“…94,96 Specifically, industry-based training for all units, workers, supervisors and union representatives inclusive of crisis and safety plans with an emphasis on wellness can contribute to reducing workplace related male suicidality and suicide. 92,94,96…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the gendered dimensions of how male first responders can effectively work through occupational traumas warrants further investigation to norm mental health help-seeking as strength-based and men looking out for each other as a masculine value. 94 More broadly, the workplace can be an ideal setting for male suicide prevention with in-service coaching about stress and anger management, relationship skills, and conflict resolution to increase the likelihood of men effectively self-managing and seeking additional help to prevent a crisis. 95 Similar to the Montreal police program in the current review, 92 workplace wellness efforts demand multiple components including prevention strategies to build social cohesion among men and reduce help-seeking stigmas.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate piece, Jewkes et al (2015b, p.118) engage specifically with Connell's (1987) much heralded hegemonic masculinities framework, and argue for interventions that "balance reflection on the power, vulnerabilities and oppression of hegemonic masculinity and positive aspects of men's aspirations". Relatedly, Seaton et al (2019) found approaches that leverage traditional (or hegemonic) masculine virtues such as physical strength, may be an effective way of engaging men in, for example, broader discussions of wellbeing, but warn against inadvertently reifying these norms. Though not directly related to healthy masculinities, Greaves (2014, p.792) found that the most effective tobacco control initiatives they studied were those that were informed by gender theory and sought to transform gender and social inequities as means of reducing tobacco consumption.…”
Section: Utilising Critical Masculinity Scholarship To Develop Theorementioning
confidence: 99%